Educação formal e a efetivação da cultura dos direitos humanos - Estevão Neto, Flávio (2018)
The objective of this research is to analyze the relationship between formal education in the face of a human rights culture, from the perspective of the conquest of human rights as historical, constructed throughout the main periods of Western History and especially in Brazil, with emphasis on the Federal Constitution of 1988. This research problematized Human Rights Education in formal education as a political proposal of the National Plan for Human Rights Education and the National Guidelines for Human Rights Education, which make up the universe of human rights culture. Its objective was to combine formal education as a vehicle for the realization of a culture of human rights, from an individual perspective, of the student as a legal entity. The right to education analyzed in this study focuses on the right to school education, as an essential function of the Democratic State of Law. In order to promote this reflection, the methodology adopted was the bibliographical review and analysis of the various international documents that deal with the subject as well as the vast national legislation. The research proposal, "formal education as a tool for the effective realization of the human rights culture", which was proven, it was verified that although several factors contribute to a bad "education", formal education is one of the tools for the effective culture of human rights